Vitamin K Antagonists, Non–Vitamin K Antagonist Oral Anticoagulants, and Vascular Calcification in Patients with Atrial Fibrillation - Peeters, Frederique E. C. M.; Dudink, Elton A. M. P.; Kimenai, Dorien M.; Weijs, Bob; Altintas, Sibel; Heckman, Luuk I. B.; Mihl, Casper; Schurgers, Leon J.; Wildberger, Joachim E.; Meex, Steven J. R.; Kietselaer, Bas L. J. H.; Crijns, Harry J. G. M. (TH Open, 2018)
Background Vitamin K antagonists (VKAs) are associated with coronary artery calcification in low-risk populations, but their effect on calcification of large arteries remains uncertain. The effect of non–vitamin K antagonist oral anticoagulants (NOACs) on vascular calcification is unknown. We investigated the influence of use of VKA and NOAC on calcification of the aorta and aortic valve.Methods In patients with atrial fibrillation without a history of major adverse cardiac or cerebrovascular events who underwent computed tomographic angiography, the presence of ascending aorta calcification (AsAC), descending aorta calcification (DAC), and aortic valve calcification (AVC) was determined. Confounders for VKA/NOAC treatment were identified and propensity score adjusted logistic regression explored the association between treatment and calcification (Agatston score > 0). AsAC, DAC, and AVC differences were assessed in propensity score–matched groups.Results Of 236 patients (33% female, age: 58 ± 9 years), 71 (30%) used VKA (median duration: 122 weeks) and 79 (34%) used NOAC (median duration: 16 weeks). Propensity score–adjusted logistic regression revealed that use of VKA was significantly associated with AsAC (odds ratio [OR]: 2.31; 95% confidence interval [CI]: 1.16–4.59; p = 0.017) and DAC (OR: 2.38; 95% CI: 1.22–4.67; p = 0.012) and a trend in AVC (OR: 1.92; 95% CI: 0.98–3.80; p = 0.059) compared with non-anticoagulation. This association was absent in NOAC versus non-anticoagulant (AsAC OR: 0.51; 95% CI: 0.21–1.21; p = 0.127; DAC OR: 0.80; 95% CI: 0.36–1.76; p = 0.577; AVC OR: 0.62; 95% CI: 0.27–1.40; p = 0.248). A total of 178 patients were propensity score matched in three pairwise comparisons. Again, use of VKA was associated with DAC (p = 0.043) and a trend toward more AsAC (p = 0.059), while use of NOAC was not (AsAC p = 0.264; DAC p = 0.154; AVC p = 0.280).Conclusion This cross-sectional study shows that use of VKA seems to contribute to vascular calcification. The calcification effect was not observed in NOAC users.
Keywords: cardiac events; computed tomographic imaging; aortic and arterial diseases; atrial fibrillation; oral anticoagulant treatment